2015
DOI: 10.4236/ajibm.2015.54018
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Mining Equipment: Key Factors for Successful Implementation

Abstract: With increasing social pressures over the past two decades, mining companies have become more concerned with occupational health and safety (OHS). This change in mentality has had an impact on the choice of new equipment introduced underground. Introduction of innovative mining equipment must now meet the double challenge of improving both productivity and OHS. However, innovative equipment does not by itself ensure success. The aim of this study is to identify the key factors that underlie successful introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Factors such as the influence of union, acceptability of emerging technologies among employees and support provided by technology firms in implementation decided whether the said technology could be adopted and implemented successfully. These factors had been suggested by Boudreau-Trudel et al (2015). The experts also opined that it was quite common that firm managers feel unsatisfied post-implementation of the technology.…”
Section: Findings and Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Factors such as the influence of union, acceptability of emerging technologies among employees and support provided by technology firms in implementation decided whether the said technology could be adopted and implemented successfully. These factors had been suggested by Boudreau-Trudel et al (2015). The experts also opined that it was quite common that firm managers feel unsatisfied post-implementation of the technology.…”
Section: Findings and Discussionmentioning
confidence: 97%
“…The authors identified several complementing factors on all the three contexts of technology, organization and environment which were missing in past research studies conducted by researchers (Gruenhagen and Parker, 2020; Boudreau-Trudel et al , 2015; Bartos, 2008), etc. These factors included technology factors such as complexity in implementation, less scope of trialability and the inability of technology firms to provide a customized solution.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stages of use of high technology for mining activities in the world are mechanization, remote steering systems, automation and robotization (Kızıl et al , 1995). There are also some studies that consider the mining sector with the advanced automation technologies (Boudreau-Trudel et al , 2014, 2015; Bellamy and Pravica, 2011). However, operations of the mining sector in many countries are maintained by small-sized enterprises and by labor-intensive activities.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%